The Influence of Implementation of E-Samsat and Tax Relief on the Motor Vehicle Taxpayer Compliance in Gianyar Regency during the Pandemic Covid-19 - Ni Made Dita Puspitari; Nyoman Sentosa Hardika; I M Wijana (Journal of Applied Sciences in Accounting, Finance, and Tax, 2022)
The aim of this research is to examine the implementation of e-samsat and tax relief on the motor vehicle taxpayer compliance in Gianyar Regency during the pandemic covid-19. This research used questionnaires method to collect the primer data. The questionnaires were distributed in Gianyar Samsat Office, in the form of 100 samples of motor vehicle taxpayers by using Slovin’s formula. The accidental sampling technique was applied to collect the samples. This research used statistical tests which are validity test, reliability test and normality test. Multiple linear regression technique was applied in this research as well as hypothetical test in the form of t and F. The finding indicated that the implementation of e-samsat and tax relief gave a positive and significant impact on motor vehicle taxpayer compliance. The implementation of e-samsat and the provision of motor vehicle tax relief will be able to increase the compliance of motorized vehicle taxpayers. Further researchers can expand the research variables in order to describe the research object completely.